Outcome of Cancer-Associated Venous Thromboembolism Is More Favorable among Patients with Hematologic Malignancies than in Those with Solid Tumors - Lecumberri, Ramón; Ruiz-Artacho, Pedro; Tzoran, Inna; Brenner, Benjamin; Farge-Bancel, Dominique; Ay, Cihan; Rosa, Vladimir; Francisco, Iria; Hernández-Blasco, Luis Manuel; Trujillo-Santos, Javier; Monreal, Manuel; the RIETE Investigators (Thrombosis and Haemostasis, 2022)
Background The natural history of patients with hematologic cancer and venous thromboembolism (VTE) has not been consistently evaluated. We aimed to compare the rates of symptomatic recurrent VTE, major bleeding, or death during anticoagulant therapy in patients with VTE associated with hematologic versus solid cancers.Methods Consecutive patients with active cancer recruited in RIETE were evaluated. Their baseline characteristics, treatments, and outcomes during the course of anticoagulation were compared. Univariate and multivariate competing-risk analyses were performed.Results As of December 2020, 16,694 patients with cancer and VTE were recruited. Of these, 1,062 (6.4%) had hematologic cancers. Hematologic patients were less likely to initially present with pulmonary embolism (46 vs. 55%) and more likely with upper extremity deep vein thrombosis (25 vs. 18%). They also were more likely to have severe thrombocytopenia at baseline (5.6 vs. 0.7%) or to receive chemotherapy (67 vs. 41%). During the course of anticoagulation (median, 150 vs. 127 days), 1,071 patients (6.4%) developed VTE recurrences, 806 (4.8%) suffered major bleeding, and 4,136 (24.8%) died. Patients with hematologic cancers had lower rates of recurrent VTE (rate ratio [RR]: 0.73; 95% confidence interval [CI]: 0.56–0.95), major bleeding (RR: 0.72; 95% CI: 0.53–0.98), or all-cause death (RR: 0.49; 95% CI: 0.41–0.57) than those with solid cancers. Patients with multiple myeloma showed the best outcomes.Conclusion Patients with hematologic cancers, particularly multiple myeloma, and VTE had better outcomes than those with solid cancers. These findings are relevant for the interpretation of previous clinical trials and the design of future studies.
Keywords: bleeding; cancer; hematologic malignancies; recurrence; venous thromboembolism